2021
DOI: 10.1002/pan3.10215
|View full text |Cite
|
Sign up to set email alerts
|

Urban green space soundscapes and their perceived restorativeness

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 70 publications
(96 reference statements)
0
33
0
Order By: Relevance
“…The research findings vary from study to study. In the case of study areas located in natural urban landscape it was observed that in the presence of bird sounds people pay less attention to road traffic noise [35] yet only in the case of people who were generally insensitive to street noise. Interestingly, according to a Czech study on the walking speed along streets with adjacent vegetation with audible bird sounds pedestrians tend to walk slower in spring [36].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The research findings vary from study to study. In the case of study areas located in natural urban landscape it was observed that in the presence of bird sounds people pay less attention to road traffic noise [35] yet only in the case of people who were generally insensitive to street noise. Interestingly, according to a Czech study on the walking speed along streets with adjacent vegetation with audible bird sounds pedestrians tend to walk slower in spring [36].…”
Section: Introductionmentioning
confidence: 95%
“…The relevant factors include local topography, location of buildings, landscaping features in the adjacent area and vegetation (specifically the type, density and height) [33,34]. Studies on the effect of noise and its reduction on wellbeing of people in urban parks, taking into consideration bird sounds were carried out in several countries, including Australia [35], the Czech Republic [36] and Sweden [37]. The research findings vary from study to study.…”
Section: Introductionmentioning
confidence: 99%
“…The well-established impact of nature on positive mood is also indicative of a positive effect on wellbeing [7][8][9]. Although some of this impact could be due to better air quality, to increased physical activity in green spaces, or to other stress-reducing mechanisms (e.g., calming natural soundscapes [10]), much of it is presumed to be a consequence of the visual information presented by natural environments, because immersion in nature is not required for a positive impact.…”
Section: Introductionmentioning
confidence: 99%
“…This was necessary to limit the duration of the experiment and prevent 'questionnaire fatigue' (Rolstad et al, 2011). While our design prevents us assessing the impacts of the presence/absence of birdsong on attentional outcomes there is already evidence that birdsong is associated with attention restoration (Ratcliffe et al, 2013(Ratcliffe et al, , 2016Uebel et al, 2021). Moreover, our design reflects the reality that most urban parks and green-spaces contain birds, and our core objective of testing how changes in the magnitude of biodiversity influences attentional outcomes.…”
Section: Limitationsmentioning
confidence: 99%